Development of GIS-based Python scripts to calculate a water surface profile on a landscape for wetlands decision-making - Wang, Zhentao; Trauth, Kathleen M. (Journal of hydroinformatics, 2020)
Wetlands provide many benefits for humans and the natural environment, but land-use changes have reduced their number and areal extent. Interest has grown in examining the landscape to determine those locations where, with minimal effort, it might be possible to develop a mitigation wetland – a location with sufficient water over a sufficient period of time to develop and maintain wetland functioning. This paper proposes a methodology to support the examination of the landscape for mitigation purposes through the application of open channel hydraulics principles to flow over a landscape. The methodology is part of a larger research effort ultimately combining hydrology and hydraulics, along with the landscape processes of infiltration and evapotranspiration, to perform a water balance assessment. Specifically, the methodology is implemented through readily available geographic information system tools along with Python scripts written for this study. The Python scripts automatically extract landscape characteristics from a digital elevation model and calculate hydraulic parameters that are used to determine water surface profiles using the Modified Euler's method. Multiple tests show that the script accurately produces profiles of flow between depressions over a landscape. Such determinations are the first step in understanding where water might exist on the surface to support mitigation wetland functions.